Chondrolipoma of tongue - Goel, G; Khadilkar, UN; Kumar, S (Kathmandu University Medical Journal, 2009)
Although lipomas can occur in any part of the body, they are found infrequently in the oral cavity. Variants of lipoma have been described according to the type of tissue present; a lipoma with cartilaginous metaplasia is a chondrolipoma which is a rare variant. We describe a chondrolipoma of tongue in a 36 year old lady. Key words: Tongue, Chondrolipoma doi: 10.3126/kumj.v6i4.1745 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 505-507